High electrochemical performance of ink solution based on manganese cobalt sulfide/reduced graphene oxide nano-composites for supercapacitor electrode materials. Issue 31 (13th July 2022) - Thanh Tam, Le Thi; Tung, Doan Thanh; Nguyet, Ha Minh; Ngoc Linh, Nguyen Thi; Dung, Ngo Thanh; Van Quynh, Nguyen; Van Dang, Nguyen; Vernardou, Dimitra; Le, Top Khac; Tuan, Le Anh; Minh, Phan Ngoc; Lu, Le Trong
Abstract : Large scale supercapacitor electrodes were prepared by 3D-printing directly on a graphite paper substrate from ink solution containing manganese cobalt sulfide/reduced graphene oxide (MCS/rGO) nanocomposites. Abstract : Large scale supercapacitor electrodes were prepared by 3D-printing directly on a graphite paper substrate from ink solution containing manganese cobalt sulfide/reduced graphene oxide (MCS/rGO) nanocomposites. The MCS/rGO composite solution was synthesized through the dispersion of MCS NPs and rGO in dimethylformamide (DMF) solvent at room temperature. Their morphology and composition were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray diffraction (EDS). The role of rGO on decreasing charge transfer resistance and enhancing ion exchange was discussed. The MCS/rGO electrode exhibits an excellent specific capacitance of 3812.5 F g −1 at 2 A g −1 and it maintains 1780.8 F g −1 at a high current density of 50 A g −1 . The cycling stability of the electrodes reveals capacitance retention of over 92% after 22 000 cycles at 50 A g −1 .